Managing adverse events associated with vismodegib in the treatment of basal cell carcinoma. (January 2017) - Fife, Kate; Herd, Robert; Lalondrelle, Susan; Plummer, Ruth; Strong, Amy; Jones, Sarah; Lear, John T
Basal cell carcinomas are the most common form of skin cancer. Some develop into advanced cases not suitable for standard therapy. Vismodegib is the first-in-class oral hedgehog pathway inhibitor (which is dysregulated in 90% of basal cell carcinomas), and has demonstrated efficacy for advanced disease in clinical trials. An UK expert panel met to discuss management strategies for adverse events associated with vismodegib (most commonly taste disturbances, muscle cramps and alopecia). Managing patient expectations and implementing treatment breaks were considered important strategies. Quinine was useful to alleviate muscle cramps. For taste disturbances, food swaps alongside dietician referral were suggested. The experts concluded that these common adverse events can be successfully managed to allow optimum treatment duration of vismodegib.